High Fiber Enrichment of Khao-Tang as a Thai Style Rice Cracker using Red Seaweed (Gracilaria gracilis) - Sumana, B.; Hirunkerd, W.; Tubklang, R.; Luekaewma, N. (International Journal of Agricultural Technology, 2018)
The develop a fibre enriched Khao-Tang, a Thai style rick cracker that is desireable for adults and children was investigated. Five different amounts of powdered Gracilaria (red algae) were added to 200 grams of Jjasmine rice and 2 grams of cassava flour (0, 5, 10, 15 and 20 grams or 2.5%, 5.0%, 7.5% and 10%). Complete randomized design (CRD) was used to determine the optimum level of powdered Gracilaria for rice crackers. Physicochemical characterization was determined for all treatments. Sensory acceptability was undertaken with 30 untrained panelists. Results of sensory evaluation, using 9-point hedonic scale, found that the highest color score was derived from crackers containing 2.5-5%, powdered Gracilaria. The highest texture score was found in the control.The highest overall score for acceptability was found in crackers containing 2.5% powdered Gracilaria.Increasing the amount of powdered Gracilaria in the rice crackers inproved the fibre content, but product quality slightly deceased, in terms of texture, color and overall acceptance.The study showed that rice crackers containing 2.5% powdered Gracilaria should be the optimum formula to consider, having a hedonic score of 7.00±1.11. In 100 gram samples, moisture, protein, lipid, carbohydrates, fibre and ash content were 3.92±0.13g, 7.60±0.17g, 17.80±2.12g, 66.91±2.12g, 2.34±0.42 g, and 1.40±0.14g, respectively. Color values for L* a* and b* were 19.88±0.69, -1.02±0.39 and 5.97±0.39, respectively. Its fracturability and energy were 10.35±0.84 N and 509.27±8.96 kcal/g, respectively.